Uncoupling effect of protonophoric and nonprotonophoric analogs of carbonyl cyanide phenylhydrazone on mitochondrial oxidative phosphorylation - Antalík, M; Sturdík, E; Sulo, P; Propperová, A; Mihalovová, E; Podhradský, D; Dzurila, M (General physiology and biophysics, 1988)
Analogs of carbonyl cyanide phenylhydrazone providing no reaction with nucleophilic groups and lacking acidobasic properties, respectively, were synthesized for study of mechanism of uncoupling effect on oxidative phosphorylation. Their retention, influence on proton transport, abilities to SH--groups modify and to stimulate respiration in rat liver mitochondria, together with their physico-chemical properties, namely lipophilicity, acidobasicity and reactivity were characterized. The substitution of acidic hydrogen of the imino group resulted in the loss of both acidobasicity and uncoupling effect on oxidative phosphorylation. A decreased reactivity resulted from the substitutions of nitrile groups with the uncoupling activity remaining preserved.
Keywords: Mitochondria, Liver; jaterní mitochondrie; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; Animals; Oxidative Phosphorylation; Rats; Structure-Activity Relationship; oxidativní fosforylace; Kinetics; zvířata; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; nitrily; kinetika; Nitriles